Mini-Percutaneous Cystolithotripsy (mPCCL) for Vesical Stone in Preschool children: Our Experience in SOMCH (Bangladesh Journal of Urology, 2025)
Background: Pediatric bladder stone disease is common in certain regions Asia. Traditionally, pediatric bladder stones have been managing by open surgeries due to narrow caliber of the urethra. However a percutaneous suprapubic approach to the bladder circumvents the problem of urethral caliber in these situations.Aim: The aim of the study was to manage vesical calculus in children by mini-percutaneous cystolithotripsy (mPCCL).Patients and Methods: Twenty children presenting with bladder stones underwent mini-percutaneous suprapubic cystolithotripsy (mPCCL) between January 2020 and June. The age ranged from 2 to 5 years and all of them were male. The stone size ranged from 1 to 4 cm.  The procedure was done under general anesthesia, and the equipment was the same as for upper tract endourology. The bladder was distended with saline and a suprapubic puncture made. The nephroscope was introduced after tract dilation and the stone removed, intact if small or after fragmentation if >1 cm. A suprapubic catheter was left in for 48 hours and perurethral catheter for 5 days.Results: All patients had an uneventful recovery following stone removal. Complete clearance was achieved in all patients while the mean duration of surgery was 35.6 + 8.95  min with range of 20-60 min. The mean hospital stay was 1.5+ 0.65 days.Conclusion: Mini-percutaneous cystolitholapexy is a minimal invasive procedure that reduces morbidity and hospital stay and. It is suitable among children with high success rate and minimum complications like postoperative fever, hematuria, urinary leakage and pain.Bangladesh J. Urol. 2024; 27(2): 89-94